Correlation of Aerobic Exercise and High Nitrate Diet with Population of Eschericia Coli in the Digestive Tract of Liver Cirrhosis Individuals - Retti Nurlaili; Syifa Mustika (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2017)
Background: In liver cirrhosis, the population of E coli is increased. conditions such as reduced intestinal). Escherichia coli with 2 enzyme nitrate reductase (NRF and Nir) reduce nitrate to nitrite and subsequently converted to ammonia (99%) and nitric oxide (1%) in anaerobic condition. Regular aerobic exercise 2-3 times/week for 30 minutes resulted in increased 2,3-DPG which reduces the activity of E. coli to reduce nitrate to nitrite and ammonia, which only works on the anaerobic state. High Nitrate Diets lead to increased nitrate reducing bacteria such as E. coli resulting in the reduction of nitrate excess produce nitrite and ammonia in large quantities. Probiotic Lactobacillus spp. can suppress the growth of bacterial endotoxins and pathogens such as E. coli and other Enterobacteriaceae. This study aimed to determine the correlation of aerobic exercise and a high nitrate diet in gastrointestinal populations of Escherichia coli gastrointestinal tract in patient with liver cirrhosis.Method: This was a descriptive-experimental study in liver cirrhosis patients Child Pugh A/B in outpatient clinic Saiful Anwar Hospital in August 2015. Respondents were asked to fill out a questionnaire with information about the demographic data, the nitrate diet, aerobic exercise, other medical data and sanitation, and stool samples were taken for faecal culture. Eta Correlation statistical test was used to determine the correlation of aerobic exercise and a high nitrate diet high in population of E. coli. The significant difference are indicated by p 0.005.Results: A total of 36 patients diagnosed with liver cirrhosis Child Pugh A/B, 14 (39%) underwent aerobic exercise 3x /week, as many as 25 (70%) consume a high nitrate diet. There was a strong relationship between aerobic exercise and high nitrate diet with population of E. coli (Ƞ = 0.725; p 0.05).Conclusion: There was a strong relationship between aerobic exercise and high nitrate diet with a population of E. coli in liver cirrhosis. Giving probiotics in patients with liver cirrhosis suppressed the population of E. coli.